CNTO6785, a fully human antIInterleukin 17 monoclonal antibody, in patients with rheumatoid arthritis with inadequate response to methotrexate: A randomized, placebo-controlled, phase II, dose-ranging study - Philip J. Mease (2018)
Copyright © 2018. All rights reserved. Objective: To evaluate the efficacy, safety, pharmacokinetics, and immunogenicity of CNTO6785, a fully human monoclonal antibody that binds to human interleukin 17A, in patients with active rheumatoid arthritis (RA) with inadequate response to methotrexate (MTX) therapy. Methods: This randomized, double-blind, placebo-controlled, dose-ranging study enrolled patients aged 18 to 80 years (inclusive) with active RA (≥ 6/66 swollen and ≥ 6/68 tender joints) who were refractory to MTX treatment (7.5-25 mg weekly, inclusive). The study duration was 38 weeks, containing a 10-week safety followup. Patients were randomized 1:1:1:1:1 to receive CNTO6785 15, 50, 100, or 200 mg every 4 weeks + MTX or placebo + MTX. The primary endpoint was American College of Rheumatology 20 (ACR20) response at Week 16. Results: There were no significant differences from placebo in the proportion of patients treated with CNTO6785 in the primary endpoint of ACR20 response at Week 16. There were no significant findings in any additional efficacy variables through Week 32. No dose-response relationships or specific patterns were observed in adverse event profiles among CNTO6785 treatment groups. Infections occurred with similar frequency across all groups, and injection site reactions were mild or moderate and did not demonstrate a dose-response relationship. Median serum CNTO6785 concentration increases through Week 38 were about dose-proportional; the incidence of neutralizing antidrug antibodies was 19.4% and was not associated with study drug dose level. Conclusion: CNTO6785 was well tolerated, but did not demonstrate clinical efficacy in patients with active RA with inadequate response to MTX.